CAMPUR KODE BAHASA SUNDA KE DALAM BAHASA INDONESIA PADA TUTURAN SISWA KELAS VII SMP NEGERI 1 KELUMBAYAN BARAT TANGGAMUS TAHUN PELAJARAN 2011/2012 - eneng lintar fandesta; karomani karomani; siti samhati (FKIP Universitas Lampung, 2013)
The problem in this research was mixed of Sundanese code into Indonesian language to the speech of the students‟ speech class VII of SMP Negeri 1 Kelumbayan Barat Tanggamus. The objective of this research was to describe the forms of mixed code. The design of this research was descriptive qualitative, which is by explaining the object research situation based on the real facts. The source of this research was the students‟ speech class VII of SMP Negeri 1 Kelumbayan Barat Tanggamus. The data in this research was in form of mixed code of Sundanese language into Indonesian language in the speech of students‟ speech class VII SMP Negeri 1 Kelumbayan Barat Tanggamus. The result of this research showed that mixed code that done by the students include the basic form of word and the form of infix. The factors that caused of mixed code were background and language of speaker‟ attitude. Furthermore, foud that there were twenty one data of mixed code that done by the students with 20 forms of basic word and 1 form of infix. Mixed code that had the primary meaning of lexical items amounted of 7 and secondary meaning was 14.Key words: mixed code, student‟ speech class VII of SMP Negri 1 Kelumbayan Barat Tanggamus.